Pengaruh Motivasi dan Loyalitas Crew Kapal terhadap Durasi On Duty & Off Duty pada PT. Pertamina Marine Solutions Jakarta - Winda Harisa; M Aji Luhur Pambudi; Ratna Kurnia Dewi; Yagie Alfayed (JURNAL TRANSMA, 2026)
This study is driven by the high rate of over PKL (over-duty periods) among ship crew members, reaching approximately, as well as the extended standby durations exceeding three months at PT Pertamina Marine Solutions Jakarta. The objective of this research is to examine the influence of work motivation and crew loyalty on the duration of work (on duty) and rest periods (off duty), as well as their effects on operational efficiency and the well-being of the crew. A quantitative approach was employed, with a population of 1.801 crew members from PT Pertamina Marine Solutions Jakarta. A total of 92 respondents were selected using the Simple Random Sampling (SRS) technique. Data were gathered through interviews, questionnaires, and literature reviews, and analyzed using multiple linear regression with SPSS version 27. The resulting multiple linear regression equation is Y = 6.327 + 0.377 (X1) + 0.451 (X2). The partial T-test results indicate that work motivation (X1) has a significance level of 0.001 < 0.005 and a t-value of 4.151 > t-tabel 1.986, demonstrating a positive and significant influence on both on-duty and off-duty durations. Consequently, Ho1 is rejected, and H1 is accepted. Likewise, crew loyalty (X2) has a significance level of 0.001 < 0.005 and a t-value of 4.952 > t- tabel 1.986, indicating a positive and significant effect on both on-duty and off-duty durations, leading to the rejection of Ho2 and acceptance of Ha2. The F-test results show that work motivation and loyalty together have a significant effect on the on- duty and off-duty durations, contributing 66,4%. The study recommends that the company strengthen its motivation and loyalty programs to enhance operational efficiency and the well-being of the crew.